5-FINGER HYPNOTIC EXERCISE TO REDUCE ANXIETY IN STUDENTS OF SMK MATILDA RUTENG - Iwa, Kornelia Romana; Andrian Beo, Yosef; Hepilita, Yohana; Xaverius Meku, Fransiskus (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Anxiety is a common problem faced by many students, including at SMK Matilda Ruteng. Excessive anxiety can interfere with learning concentration, academic performance, and students' mental well-being. The purpose of this PKM is to reduce the level of anxiety in students of SMK Matilda Ruteng through 5 finger hypnosis exercises. This PKM was carried out by involving Matilda Ruteng Vocational High School students as participants. The PKM team explained the 5 finger hypnotic technique and its benefits for reducing anxiety. Students are given instructions on how to do the 5 finger hypnosis exercise independently. After participating in 5 finger hypnosis exercises for several sessions, students of Matilda Ruteng Vocational School showed a significant decrease in anxiety levels. They reported feeling calmer, able to face exams more confidently, and managing stress better. This PKM succeeded in proving that 5 finger hypnosis exercises can be effective in reducing anxiety in Matilda Ruteng Vocational High School students. This technique can be an effective alternative to help students deal better with academic and everyday life challenges. It is hoped that this method can be extended to other educational environments to provide wider benefits in dealing with anxiety in adolescents.